Prevalence, Pattern and Socio-Demographic Determinants of Tobacco Use in Elderly Population of a Rural Area of Central India - Tarique Ibrahim; Rashmi Bhujade; Arun K Wanjpe; Dharampal S Chouhan (Medsci Publications, 2019)
Background-India has 2nd largest tobacco consumers in the world. Tobacco use is one of the important modifiable risk factors for premature death & many diseases. There is an urgent need for protection from devastating adverse effects of tobacco use on health, society, environment & economy. Main target group for interventions is youngsters, elderly population is usually neglected. This study was planned to explore the situation of elderly population. Method- Cross sectional study was designed to estimate the prevalence, pattern and associated factors of tobacco use in 500 elderly of Ghatiya block of Ujjain. Information was collected by help of semi structured proforma. Data analysis was done with the help of SPSS -20. Chi square test was applied for checking significance. Results-Prevalence of tobacco use was 55.4% in elderly population, 31.1 % participants were using smoked tobacco, 47 % were using smokeless tobacco while 22% were dual users. It was found to be significantly associated with age, sex, religion & occupation of the participants. Conclusion-Prevalence of tobacco use was found to be more than prevalence of nation as well as state. We should also plan interventions for elderly population keeping associated factors in mind, So that we can improve quality and quantity of elderly life.